Raw cellulose/polyvinyl alcohol blending separators prepared by phase inversion for high-performance supercapacitors. (8th December 2020) - Heng, Yingqi; Xie, Tianqi; Wang, Xiyang; Chen, Ding; Wen, Jiahao; Chen, Xiyong; Hu, Dongying; Wang, Nannan; Wu, Yimin A
Abstract: The development of a biodegradable cellulose-based separator with excellent performance has been of great research significance and application potential for the green development of supercapacitors. Herein, the regenerated porous cellulose/Polyvinyl alcohol films (CP-10, CP-15, CP-20, CP-25) with different mass ratio were successfully fabricated by a simple blending and phase inversion process. Their electrochemical properties as separators in assembled supercapacitor were evaluated. Fourier transform infrared spectroscopy and x-ray diffraction analysis indicate that intermolecular and intramolecular hydrogen bonding existed between cellulose and polyvinyl alcohol of the CP films. Compared with other CP films, the CP-20 film shows higher mechanical strength (28.02 MPa), better wettability (79.06°), higher porosity (59.69%) and electrolyte uptake (281.26 wt%). These properties of CP-20 are expected to show better electrochemical performance as separator. Indeed, the electrochemical tests, including electrochemical impedance spectroscopy, cyclic voltammetry, galvanostatic charge discharge, demonstrate that the SC-20 capacitor (with CP-20 as separator) shows the lowest equivalent series resistance of 0.57 Ω, the highest areal capacitance of 1.98 F cm −2 at 10 mV s −1, specific capacitance of 134.41 F g −1 and charge-discharge efficiency of 98.62% at 1 A g −1 among the four capacitors with CP films as separators. Comparing the assembled SC-40 and SC-30 with two commercial separators (TF4040 and MPF30AC) and SC-PVA with Polyvinyl alcohol (PVA) separator, the CV and GCD curves of SC-20 maintain the quasi rectangular and symmetrical triangular profiles respectively at different scan rates in potential window of 0–1 V. SC-20 exhibits the highest value of 28.24 Wh kg −1 at 0.5 A g −1 with a power density of 0.26 kW kg −1, and 13.41 Wh kg −1 at 10 A g −1 with a power density of 6.04 kW kg −1 . SC-20 also shows the lowest voltage drop and the highest areal and specific capacitance. Moreover, SC-20 maintains the highest value of 86.81% after 4000 cycles compared to 21.18% of SC-40, 75.07% of SC-30, and 6.66% of SC-PVA, showing a superior rate capability of a supercapacitor. These results indicate that CP films can be served as promising separators for supercapacitors.